Несуча здатність та деформативність стиснутих дерев’яних елементів при локальному впливі високих температур - Пелех, Андрій Богданович (Національний університет "Львівська політехніка", 2021)
Дисертація присвячена експериментальним та теоретичним дослідженням напружено деформованому стану стиснутих дощатоклеєних колон при локальному впливі високих температур. Дослідні зразки відрізнялись ступенем вогнезахисту. Виконано натурний експеримент дослідження роботи дерев’яних конструкції під час реальної пожежі. Отримані аналітичні результати розрахунку температурної задачі та виведені рівняння для визначення локального впливу температур на несучу здатність та деформативність дерев’яних центрально стиснутих колон. Виконано розрахунок дерев’яних колон методом приведеного перерізу із використанням інструментарію методу скінчених елементів в програмному комплексі «Ліра». Результати дисертаційного дослідження застосовані під час проектування та виконання дерев’яних конструкцій на реальних об’єктах. На основі отриманих результатів експериментальних та теоретичних досліджень розроблено практичні рекомендації із розрахунку несучої здатності стиснутих дощатоклеєних колон, що працюють в умовах локальної дії високих температур. Диссертация посвящена экспериментальным и теоретическим исследованиям напряженно деформированном состояния сжатых колонн из клееной древесины при локальном воздействии высоких температур. Опытные образцы отличались степенью огнезащиты. Выполнен натурный эксперимент исследования работы деревянных конструкции в условиях реальной пожара. Полученные аналитические результаты расчета температурной задачи и выведены уравнения для определения локального воздействия температур на несущую способность и деформативность деревянных центрально сжатых колон. Выполнен расчет деревянных колон методом приведенного сечения с использованием инструментария метода конечных элементов в программном комплексе «Лира». Результаты исследования применены при проектировании и выполнения деревянных конструкций на реальных объектах. На основе полученных результатов экспериментальных и теоретических исследований разработаны практические рекомендации по расчету несущей способности сжатых колонн из клееной древесины, работающих в условиях локального воздействия высоких температур. The thesis is devoted to experimental and theoretical studies of the stress-strain state of compressed laminated columns under local exposure to high temperatures. The test specimens were distinguished by the degree of fire protection. Practical recommendations for calculating the load-carrying capacity of compressed boarded laminated columns working in conditions of local action of high temperatures have been developed. The first chapter reviews the existing experimental studies of wooden structures under the influence of high temperatures. Particular attention is paid to methods of calculation of compressed damaged wooden elements. It is found that the issue of fire resistance and operation of wooden structures under local exposure to high temperatures is not fully disclosed and requires additional research. The second chapter presents the scope and methodology of the experimental research. The method of determining the characteristics of wooden structures according to the current regulatory documents is described. To investigate the mechanical characteristics of wood in compression, tension, and bending tests were carried out on samples according to current regulations. The methodology of central compression testing of columns at temperature is described. For the study, there were made planking of the columns of size 100x100x1000 (h) mm, with planks of section 25x100 mm. The third chapter presents the results of studies of a series of test samples to determine the mechanical properties of wood in compression, tension, and bending. The results of compression tests of the laminated wooden columns under the action of normal temperatures have been obtained and analyzed. According to the results of tests of 5 and 6 series, studies of strength and deformability of compressed wooden columns on the action of local heating without protection and with the protection of the heating zone with plasterboard sheets were obtained and analyzed. The results of a full-scale test of a wooden frame under conditions of a real fire are processed. The performance of the structures at different stages of the fire was analyzed. In the fourth chapter, the calculation of wooden columns for the influence of external temperature load is carried out. An analytical solution of the problem of temperature distribution in a wooden column, part of which is in a variable in time temperature field, is obtained. The analytical solution of the problem of distribution of compressive, tensile, and shear strength of wood in the body of an unevenly, unilaterally heated wooden column has been obtained. The calculation of the stress-strain state of wooden columns during local high-temperature action and external load has been performed. The practical calculation of a centrally compressed column with a local thermal influence by the finite element method in the program complex "Lira" has been carried out. The recommendations for the calculation of wooden columns under their local fire action are given. The conclusions present the main results that reflect the scientific novelty and solution of scientific and technical problems.
Несущая способность и деформативность сжатых деревянных элементов при локальном воздействии высоких температур
Bearing capacity and deformability of compressed wooden elements under the local influence of high temperatures
Keywords: межа вогнестійкості; високотемпературний локальний нагрів; критичний вигин; дерев’яні дощатоклеєні колони; дія високої температури; дерев’яні конструкції; предел огнестойкости; высокотемпературный локальный нагрев; критический изгиб; колонны из клееной древесины; действие высокой температуры; деревянные конструкции; fire resistance limit; high-temperature local heating; critical bending; wooden laminated columns; high-temperature action; wooden structures; 624.011.14+624.046+ 624.044